Activation of functional α7-containing nAChRs in hippocampal CA1 pyramidal neurons by physiological levels of choline in the presence of PNU-120596. - Bopanna I Kalappa; Alexander G Gusev; Victor V Uteshev (PLoS ONE)
Background The level of expression of functional α7-containing nicotinic acetylcholine receptors (nAChRs) in hippocampal CA1 pyramidal neurons is believed to be very low compared to hippocampal CA1 interneurons, and for many years this expression was largely overlooked. However, high densities of expression of functional α7-containing nAChRs in CA1 pyramidal neurons may not be necessary for triggering important cellular and network functions, especially if activation of α7-containing nAChRs occurs in the presence of positive allosteric modulators such as PNU-120596. Methodology/principal findings An approach previously developed for α7-containing nAChRs expressed in tuberomammillary neurons was applied to investigate functional CA1 pyramidal α7-containing nAChRs using rat coronal hippocampal slices and patch-clamp electrophysiology. The majority (∼71%) of tested CA1 pyramidal neurons expressed low densities of functional α7-containing nAChRs as evidenced by small whole-cell responses to choline, a selective endogenous agonist of α7 nAChRs. These responses were potentiated by PNU-120596, a novel positive allosteric modulator of α7 nAChRs. The density of functional α7-containing nAChRs expressed in CA1 pyramidal neurons (and thus, the normalized net effect of activation, i.e., response net charge per unit of membrane capacitance per unit of time) was estimated to be ∼5% of the density observed in CA1 interneurons. The results of this study demonstrate that despite low levels of expression of functional pyramidal α7-containing nAChRs, physiological levels of choline (∼10 µM) are sufficient to activate these receptors and transiently depolarize and even excite CA1 pyramidal neurons in the presence of PNU-120596. The observed effects are possible because in the presence of 10 µM choline and 1-5 µM PNU-120596, a single opening of an individual pyramidal α7-containing nAChR ion channel appears to transiently depolarize (∼4 mV) the entire pyramidal neuron and occasionally trigger action potentials. Conclusions 1) The majority of hippocampal CA1 pyramidal neurons express functional α7-containing nAChRs. In the absence of PNU-120596, a positive allosteric modulator of α7 nAChRs, a lack of responsiveness of some hippocampal CA1 pyramidal neurons to focal application of 0.5-1 mM choline does not imply a lack of expression of functional α7-containing nAChRs in these neurons. Rather, it may indicate a lack of detection of α7-containing nAChR-mediated currents by patch-clamp electrophysiology. 2) PNU-120596 can serve as a powerful tool for detection and enhancement of responsiveness of low densities of functional α7-containing nAChRs such as those present in hippocampal CA1 pyramidal neurons. 3) In the presence of PNU-120596, physiological concentrations of choline activate functional CA1 pyramidal α7-containing nAChRs and produce step-like currents that cause repetitive step-like depolarizations, occasionally triggering bursts of action potentials in CA1 pyramidal neurons. Therefore, the results of this study suggest that in the presence of PNU-120596 and possibly other positive allosteric modulators, endogenous choline may persistently activate CA1 pyramidal α7-containing nAChRs, enhance the excitability of CA1 pyramidal neurons and thus act as a potent therapeutic agent with potential neuroprotective and cognition-enhancing properties.